Worry and the level of depression among patients with type 1 diabetes mellitus. The mediating role of illness acceptance - Julia Krawczyk; Michał Ziarko; Ewa Mojs; Dorota Zozulińska-Ziółkiewicz (Journal of Medical Science, 2021)
Aim. The purpose of the conducted study was to explore the role of cognitive processes, such as habitual worry, with regard to depressive mood in patients with type 1 diabetes mellitus (T1DM), as well as the significance of illness acceptance in the form of personal asset and mediator in relation between worry and depression. Material and Methods. The study involved 229 participants diagnosed with T1DM, who completed a set of self-description questionnaires. Assessment methods included The Anxious Thoughts Inventory (AnTI), The Acceptance of Illness Scale (AIS) and The Center for Epidemiologic Studies Depression Scale (CES-D). Results. The results demonstrate that worry is positively correlated with depression. What is more, the relationship between habitual worry and depression was mediated through illness acceptance. Conclusions. The impact of habitual worry on mental health in T1DM cannot be ignored. Moreover, the observed dependence suggests that depressive mood present in individuals with T1DM may persist, since overly worried patients do not accept their own illness. Strengthening patients’ acceptance of their condition and bringing up the topic of worry in the course of diabetes education, can be a powerful tool in depression prevention. Nevertheless, further research is necessary.